b ractice and theory /c - Adey, Philip (b, 2004)
This book integrates in a unique way all that is known about changing teachers' practice, the key to all educational development. All attempts to `raise standards' or to 'make schools relevant to the 21st century' rest on helping teachers to develop new skills. The Professional Development of Teachers: Practice and Theory draws on the author's 30 years of experience, on a series of new empirical studies, and on the extensive literature on staff development to develop an integrated model of effective professional development. The model relates concepts of belief change, collegiality, school ethos, school and local government leaders, as well as key features of effective PD programmes such as longevity, constructivism, theory-bases, and coaching. It has theoretical validity and can be used as a practical guide to anyone involved in educational change: teachers, researchers, curriculum innovators, school leaders, university staff, educational policy makers, local government and government Ministers. In spite of its deep scholarly roots, this book is written in a lively, accessible style. It will challenge established theoreticians in the field while providing very direct advice to practitioners.
Includes bibliographical references and index.
Keywords: v; Education; Professional Development